IMPLEMENTATION OF THE COOPERATIVE MURDER MODEL (MOOD, UNDERSTAND, RECALL, DIGEST, EXPAND, REVIEW) ORIENTED WITH LOCAL TIMOR WISDOM IN IMPROVING LEARNING OUTCOMES OF CLASS V PRIMARY SCHOOL STUDENTS - Adriana Femin; Julhidayat Muhsam (Mimbar PGSD Flobamorata, 2023)
This research aims to improve social studies learning outcomes by implementing the MURDER Cooperative Learning Model (Mood, Understand, Recall, Digest, Expand, Review) oriented towards local wisdom which can improve the learning outcomes of Class V students at SD Inpres Oepoi for the 2022/2023 academic year. The type of research used is classroom action research (PTK) with the research subjects being 20 class V students with a KKM of 70 with a success indicator of 75%. The research results showed that teacher activity in cycle I was 83% and cycle II 93%. Student activity in cycle I reached 87% and increased in cycle II to 95%. Student learning outcomes in cycle I were 68.25 with a success indicator of 55% and increased in cycle II with a KKM of 86.5 and a success indicator of 90%. Based on the research data, it can be concluded that the MURDER Cooperative learning model oriented to local wisdom can improve social studies learning outcomes for class V students at SD Inpres Oepoi, Kupang City.